Risk Assessment for Asset Owners : a Pocket Guide. - Calder, Alan (Pocket Guides: Practical Information Security., 2007)
This book is apocket guide to the ISO27001 risk assessment, and designed to assist asset owners and others who are working within an ISO27001/ISO17799 framework to deliver a qualitative risk assessment. It conforms with the guidance provided in BS7799-3:2006 and NIST SP 800-30.